2006
DOI: 10.1097/01.sle.0000202195.51699.63
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Repair of Bilateral Inguinal Hernias: A Prospective, Randomized Study of Single Versus Double Mesh Laparoscopic Totally Extraperitoneal Repair

Abstract: The aim of this study was to compare the double and the single mesh techniques, both used in the laparoscopic totally extra peritoneal (TEP) repair of bilateral inguinal hernia. Sixty-five patients with bilateral inguinal hernia were enrolled in a prospective, randomized trial comparing the single and the double mesh techniques. The single and the double mesh techniques compared favorably in terms of operating time, long-term morbidity, hospital stay, time for return to work, postoperative quality of life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…In contrast with our findings, Ohana et al [25] seroma was more encountered in the single mesh group [33.33 vs. 15.62% in the double mesh group, p < 0.05].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our findings, Ohana et al [25] seroma was more encountered in the single mesh group [33.33 vs. 15.62% in the double mesh group, p < 0.05].…”
Section: Discussioncontrasting
confidence: 99%
“…Another study showed no difference in the early and late outcomes when one or two meshes were used for the laparoscopic repair of bilateral inguinal hernias;[ 14 ] however, the cost was lower when a single mesh was used. [ 15 ] The intensity of the inflammatory response is directly proportional to the mesh size. [ 16 ] In the present study, a single mesh was used so that inflammatory responses to the mesh during the acute phase would be similar in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons are reluctant to use a single mesh. In a prospective randomized study, Ohana et al 13 studied the use of single versus double mesh repair. After an average follow-up of 21 months, there were no reports of any recurrences.…”
Section: Mesh Placementmentioning
confidence: 99%